2019
DOI: 10.1186/s12871-019-0824-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory acidosis during bronchoscopy-guided percutaneous dilatational tracheostomy: impact of ventilator settings and endotracheal tube size

Abstract: Background: The current study investigates the effect of bronchoscopy-guided percutaneous dilatational tracheostomy (PDT) on the evolution of respiratory acidosis depending on endotracheal tube (ET) sizes. In addition, the impact of increasing tidal volumes during the intervention was investigated. Methods: Two groups of ICU-patients undergoing bronchoscopy-guided PDT with varying tidal volumes and tube sizes were consecutively investigated: 6 ml/kg (N = 29, mean age 57.4 ± 14.5 years) and 12 ml/kg predicted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although the effect of appropriate ETT size on critical care outcomes is a relatively understudied question, a few groups have investigated the association of tube size with ventilator weaning and respiratory mechanics. [10][11][12] Overall, it has been shown that smaller diameter ETTs are associated with an increase in various respiratory metrics, including airway pressures and respiratory frequency to tidal volume ratios. [10][11][12] The effect of tube diameter on these metrics may be the driver behind the increased intubation duration noted in our study, although we did not observe a significant relationship between ETT size group and PIP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effect of appropriate ETT size on critical care outcomes is a relatively understudied question, a few groups have investigated the association of tube size with ventilator weaning and respiratory mechanics. [10][11][12] Overall, it has been shown that smaller diameter ETTs are associated with an increase in various respiratory metrics, including airway pressures and respiratory frequency to tidal volume ratios. [10][11][12] The effect of tube diameter on these metrics may be the driver behind the increased intubation duration noted in our study, although we did not observe a significant relationship between ETT size group and PIP.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Overall, it has been shown that smaller diameter ETTs are associated with an increase in various respiratory metrics, including airway pressures and respiratory frequency to tidal volume ratios. [10][11][12] The effect of tube diameter on these metrics may be the driver behind the increased intubation duration noted in our study, although we did not observe a significant relationship between ETT size group and PIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tracheal puncture with partially lost airway) shorter and probably safer. Another important aspect is, that with good visibility bronchoscopy is nearly unnecessary, thus it is easier to avoid the significant rise of PaCO 2 and consequent respiratory acidosis which occurs during bronchoscopy even when applying increased tidal volume and large diameter endotracheal tube (51). The obvious limitation of our study is that PDTs were made in cadavers, which could influence cartilage flexibility, so cadaver's tracheal cartilages could be more rigid than in case of living tissue.…”
Section: Discussionmentioning
confidence: 94%
“…Fiberoptic tracheo-bronchoscopy remains the standard method to perform PDT [1,2]. Obstruction of the endotracheal tube due to flexible endoscope during PDT may cause ventilation problems with subsequent hypoxemia, hypercarbia, increased intracranial pressure and pneumothorax [5]. In order to provide better visualization of the tracheal anatomy and improve airway management and safety during the PDT procedure, the rigid tracheotomy endoscope (TED) was introduced [6].…”
Section: Introductionmentioning
confidence: 99%